2019
DOI: 10.1177/0959683619857231
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations and transformations of hunter-gatherers in forest environments: New archaeological and anthropological insights

Abstract: Like any other living being, humans constantly influence their environment, be it intentionally or unintentionally. By extracting natural resources, they shape their environment and also that of plants and other animals. A great difference setting people apart from all other living beings is the ability to construct and develop their own niche intentionally, and the unique tool for this is cultural behaviour. Here, we discuss anthropogenic environmental changes of hunter-gatherers and present new palaeoecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 86 publications
(105 reference statements)
0
17
0
1
Order By: Relevance
“…Thus, recreating the situation during that period by means of GPR and geoarchaeology is our goal. Following the background of intensive research in the Northern European Plain (Groß, 2017; Groß et al, 2018, 2019; Hartz et al, 2014; Lübke et al, 2011; Schmölcke, 2016; Schmölcke and Nikulina, 2015), this paper provides a first reconstruction of the paleotopography and stratigraphy of parts of the bog during the early Mesolithic using geophysics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, recreating the situation during that period by means of GPR and geoarchaeology is our goal. Following the background of intensive research in the Northern European Plain (Groß, 2017; Groß et al, 2018, 2019; Hartz et al, 2014; Lübke et al, 2011; Schmölcke, 2016; Schmölcke and Nikulina, 2015), this paper provides a first reconstruction of the paleotopography and stratigraphy of parts of the bog during the early Mesolithic using geophysics.…”
Section: Introductionmentioning
confidence: 99%
“…Al mismo tiempo se ha argumentado que la ocupación recurrente de ciertos sitios por parte de los cazadoresrecolectores lleva a modificar el entorno, favoreciendo la presencia de especies que fueron aprovechadas y desechadas en ese mismo lugar. Se logra así, de manera no intencional, que en las cercanías de un sitio se desarrollen aquellas especies regularmente explotadas, dando lugar a huertos silvestres (wild orchads según Politis, 2007:145-153;ver también Gnecco, 2000y Groß et al 2019. No se han comprobado casos de este tipo para los bosques patagónicos, pero Belmar et al (2017) argumentan que:…”
Section: Vegetalesunclassified
“…Focus 2 Transformation of socio-economic formations addresses, in different spatial and temporal case studies, the ongoing socio-environmental changes as observed within different social formations. Studies of ‘Complex Foragers’ relate to the adaption and niche manipulation in Palaeo- and Mesolithic forested and aquatic environments as well as technological change (Eriksen et al, this issue; Groß et al, this issue, 2018a, 2018b; Mevel et al, this issue; Sørensen et al, 2018; Sommer et al, 2018). ‘Horticulturalists’ are investigated with respect to the temporal dimension of Linearbandkeramik houses and settlements (Meadows et al, this issue), the monumental expression of socio-cultural and technological transformations (Brozio et al, this issue) and the concept of Neolithisation itself (Blank et al, 2018; Terberger et al, 2018).…”
Section: The Approach To the Scales Of Socio-environmental Transformation In Prehistoric And Archaic Societiesmentioning
confidence: 99%
“…Focus 3 Socio-environmental components of change concentrates on specific factors or components of change, be they climate and human adaptation strategies (Butruille et al, 2017; Groß et al, this issue; Hinz et al, this issue; Schirrmacher et al, 2019); vegetation and faunal change, human impact, and resource management (Dal Corso et al, this issue, 2018; Feeser et al, this issue; Sommer et al, 2018; Wieckowska-Lüth et al, 2018); the dynamics of soils and erosion processes, demography, mobility and diseases (Capuzzo et al, 2018; Feeser et al, this issue; Fuchs et al, this issue; Furholt, 2017; Krause-Kyora et al, 2018; Müller and Diachenko, 2019); the development and impacts of subsistence practices (Filatova et al, 2019; Filipović et al, this issue, 2018; Jahns et al, 2018) or the social role of technologies and innovations (Bech et al, 2018; Brozio et al, this issue; Kirleis, 2019; Schaefer-Di Maida and Kneisel, this issue).…”
Section: The Approach To the Scales Of Socio-environmental Transformation In Prehistoric And Archaic Societiesmentioning
confidence: 99%
See 1 more Smart Citation